First person singular : papers from the Conference on an Oral Archive for the History of American Linguistics. (Charlotte, N.C., March 1979) - Davis, Boyd H.; O'Cain, Raymond K. (Amsterdam studies in the theory and history of linguistic science. Studies in the history of linguistics, 1980)
This volume consists of autobiographical by the following scholars, together with pictures and autographs: Raven I. McDavid, Jr., Henry M. Hoenigswald, John B. Carroll, William G. Moulton, Archibald A. Hill, Yakov Malkiel, Charles F. Hockett, Harold B. Allen, William Bright, Einar Haugen, George S. Lane, Frederic G. Cassidy, James B. McMillan, Winfred P. Lehmann, Fred W. Householder, and Dell Hymes. A master list of references, and an index of persons conclude the volume.